Deteksi sebaran gas metana (CH4) di TPA Pakusari Jember menggunakan sensor TGS 2611 (Detection of methane gas (CH4) distributionin at TPA Pakusari Jember using TGS 2611 sensor) - Sri Indariyatul Masruroh; Bowo Eko Cahyono; Agung Tjahjo Nugroho (Department of Physics – Universitas Negeri Padang UNP, 2019)
Waste is an important issue in urban environments and will continue to be faced by governments and communities. Most waste disposal sites are concentrated in the Final Disposal Site (TPA). Waste accumulation in the landfill can create methane gas which can spread to the environment. The purpose of this research is to know the application of TGS 2611 sensor as methane gas detector and use it to measure methane gas distribution at TPA Pakusari Jember. This research is conducted by detecting the distribution of methane gas in TPA Pakusari. Data retrieval is performed by placing the sensor directly above the garbage pile and then observe the voltage value that appears on the LCD screen. The obtained data of voltage values are normalized and then they are visualized into 2 dimension contoure graph by using Matlab application. The results show that methane gas in TPA Pakusari is not spread evenly but it spreads randomly. This is due to the unequal garbage composition and the height random garbage at each measurement point. The largest methane gas is located in the area of the pile of organic waste that suffers from decay and the lowest methane gas is located in areas with little piles of rubbish and dominant with the soil. Thus it can be concluded that TGS 2611 sensor can be applied to detect the spread of methane gas in TPA Pakusari Jember.